Misformation Error Found in Student’s recount text Writing - Gau, Yustinus; Maharani, Putu Devi; Nugraha, IGB Wahyu (Humanis; Vol 25 No 2 (2021), 2021)
This study is aimed to find out the misformation error type and causes of errors in writing recount text by the ninth-grade students of SMP Raj Yamuna Denpasar. In this study, the researcher used the theory from Dulay, Burt & Krasen (1982) about the types of error and the theory from Richards (1974) to find out the causes of errors.  Based on the result of this study, there were found 36 errors of misformation in writing recount text made by the students. The factors that influence the error in writing recount text made by the students were; a succession of approximative system with the percentage of 47.6%, intralingual interference with the percentage of 35.7%, and universal hierarchy of difficulty with the percentage of 16.6%